PERAN SATPAS DALAM RANGKA PELAYANAN PRIMA GUNA TERWUJUDNYA KEPUASAN MASYARAKAT - Nurwito Saputri, Fajar Pratiwi Gentur (Advances in Police Science Research Journal, 2020)
ABSTRACT This research aims to determine how the roles and factors that influence the first-rate services of Bandung city police administration unit to create community satisfaction. The background in this research is the main task and function of the POLRI as a public servant, as well as the Bandung city police which is the research location. So that the Bandung City Police administration unit becomes the center of research because there are still complaints, criticism, and other negative opinion in various mass media and social media. This study uses a qualitative approach with data collection methods in the form of interviews, observations, and document studies. To support and strengthen the data obtained, researchers used questionnaire data collection techniques with 122 respondents to answer several questions related to community satisfaction in the context of excellent service conducted by the Bandung City Police administration unit. This research refers to UU No. 2 of 2002, UU No. 25 of 2009 and KEMENPAN No. 63 of 2003 as an excellent service standard provided by the Satpas Polrestabes Bandung to realize community satisfaction. The results of this study are the implementation of the role of the Satpas Polrestabes Bandung is still not going well in providing excellent service to the community, because of the four standard indicators used as a reference there is only one indicator that has been fulfilled, namely the position of people in behaviour. Factors that influence the role of the Bandung City Police administration unit in excellent service consist of 14 elements that are divided into ten factors that still need to be improved and four parts that have been fulfilled, such as legal basis, precise requirements, service products and service guarantees that provide service certainty. Thus, some suggestions were put forward by researchers to support the implementation of the Bandung Polrestabes mission to realize the vision that has been set, namely the realization of excellent service to the community in law enforcement efforts and the maintenance of security and order to increase public trust. Keywords : the role, excellent service, community satisfaction.